Production control - Sauna-aho, Juha (My University, 2012)
This thesis analyzes important concepts in production control from the perspective of a typical manufacturing plant. The scope is further limited to include theory that is especially relevant for the case company. The case company is an electric motor manufacturer ABB Oy, Motors and Generators Vaasa. The purpose of the research is first to develop understanding of theoretical concepts regarding production control. Secondly the case company will be used as an example to show some applications of the concepts discussed. The goal is to find the most effective tools for the development of the case company’s production control. The research is divided into three parts: a theoretical part based on literature on production control, to the analysis of the case company’s production control and to a simulation study. The main focus will be given to principles that are directly applicable by the management of a manufacturing plant. The purpose of simulation will be to further increase the understanding of the theory discussed and to show the contrast of some varying production control configurations. The research problem is: How can theoretical frameworks regarding production control be used for significant improvement in a typical manufacturing plant such as the case company? By discussing and clarifying many of the practical activities and processes in production control with a theoretical framework, the research shows that understanding such a framework can give managers valuable insights and perspectives for the development of processes.
Keywords: Production control; operations management; variability; operations research; queuing theory.; fi=Tuotantotalous|en=Industrial Management|